Calibration-Free Second Harmonic Generation (SHG) Image Analysis for Quantification of Trace Crystallinity Within Final Dosage Forms of Amorphous Solid Dispersions. Issue 11 (November 2018) - Smith, Casey J.; Dinh, Janny; Schmitt, Paul D.; Stroud, Paul A.; Hinds, Jeremy; Johnson, Michael J.; Simpson, Garth J.
A statistical model enables auto-calibration of second harmonic generation (SHG) images for quantifying trace crystallinity within amorphous solid dispersions (ASDs) over a wide dynamic range of crystallinity. In this paper, we demonstrate particle-counting approaches for quantifying trace crystallinity, combined with analytical expressions correcting for particle overlap bias in higher crystallinity regimes to extend the continuous dynamic range of standard particle-counting algorithms through to the signal averaging regime. The reliability of the values recovered by these expressions was demonstrated with simulated data as well as experimental data obtained for an amorphous solid dispersion formulation containing evacetrapib, an Eli Lilly and Company compound. Since particle counting independently recovers the crystalline volume and the SHG intensity, the average SHG intensity per unit volume can be used as an internal calibrant for quantifying crystallinity at higher volume fractions, for which particle counting is no longer applicable.